Genome-wide analysis of polygalacturonase gene family from pear genome and identification of the member involved in pear softening - Zhang, Suling; Ma, Min; Zhang, Huping; Zhang, Shaoling; Qian, Ming; Zhang, Zhen; Luo, Weiqi; Fan, Jinbu; Liu, Zhiqiang; Wang, Libin (BMC plant biology, 2019)
Polygalacturonase (PG), as an important hydrolase participating in the degradation of pectin, plays an important role in softening process of fruit. However, information on PG gene family in pear genome and the specific member involved in fruit softening is still rudimentary. In this study, a total of 61 PG genes, which could be divided into six subclasses, were identified from the pear genome with diverse chromosome locations, gene structures, motifs and cis-acting elements. Most PbrPGs were derived from WGD/segmental duplication blocks, and purifying selection was the main driving force for their expansion. The expression profiles of PbrPGs in pear were tissue/development-stage/cultivar-dependent. During 'Housui' pear storage, associated with the reduction of firmness was the accumulation of PG activity. Totally, 28 PbrPGs were expressed during fruit storage, which could be classified into five categories based on different expression patterns; most demonstrated an increased trend. Of these, PbrPG6 were proposed to account for pear softening in combination of the phylogenetic and correlation analysis among firmness, PG activity and PbrPGs. By constructing the silencing vector, a higher firmness was observed in PbrPG6-silenced fruit when compared with that of the control (empty vector). In a further study, we found that the expression of PbrPG6 was regulated by postharvest 1-MCP/ethrel treatment, and several PbrERFs might function in this process. We identified 61 PbrPG genes from pear genome; of these, PbrPG6 was involved in fruit softening process; furthermore, the expression of PbrPG6 might be under the control of PbrERF. This study provides a foundation for future work aimed at elucidating the molecular mechanism underlying pear softening.